Action research living theory - Whitehead, Jack (SAGE Publications, 2006)
In Action Research: Living Theory, Jean McNiff and Jack Whitehead set out their vision for action research in the 21st Century. This is a passionate, and compelling book, that defines the philosophy behind action research and the process of doing action research for all those interested in this fast growing area. It sets in place the foundations of action research as a discipline, and roots action research as a compassionate , ethical and politically-engaged form of enquiry. McNiff and Whitehead's book will be essential reading for all those with an interest in Action Research.